Strategi Perekrutan Dalam Meningkatkan Kinerja Karyawan Pada Usaha Rumah Makan Padang Jaya - Hilma Harmen; Alifya Dzihni Innayah C; Dinni Ria Anggita; Ika Khairi Dzaky Nasution; Muhammad Afdal; Rotua Julianti Simare Mare; Siti Yusriah; Winadya Norma Septelina Simare Mare; Yulan Hutabarat (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Recruitment of labor is an important part of running a business. Like in Padang Jaya Restaurant. However, the recruitment process in this MSME still faces various obstacles, such as limited recruitment methods. This study aims to analyze the recruitment strategy implemented at Rumah Makan Padang Jaya and identify the challenges faced. This research method uses a qualitative method with direct interviews with the owner of the restaurant. The results showed that the recruitment process at Rumah Makan Padang Jaya still relies on recommendations from family, friends, and acquaintances, as well as opening job vacancies directly at the business location. Although this method can reduce recruitment costs, the restaurant certainly gets limited candidates. In addition, recruitment is done directly by the owner without a special team, so the process is less systematic. To improve the effectiveness of recruitment, it is recommended that these MSMEs utilize online job search platforms, cooperate with job training institutions, and form a more structured recruitment team.